2021
DOI: 10.1080/21655979.2021.1968777
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoporin 160 (NUP160) inhibition alleviates diabetic nephropathy by activating autophagy

Abstract: Diabetic nephropathy (DN) is the leading cause of end-stage renal disease worldwide. Autophagy was reported to be related to the pathogenesis of DN. This research investigated the function of the Nucleoporin 160 (Nup160) gene in regulating autophagy in DN. A mouse model of DN was established through an intraperitoneal injection of streptozotocin (STZ). Normal rat kidney tubular epithelial cells (NRK-52E) were treated with high glucose to induce DN in vitro. Real-time quantitative polymerase chain reaction (RT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The study also found that NF-kB, in addition to its role mediated by TLR4, is a transcription factor that plays an important role in inflammation, immunity, cell proliferation, differentiation, and survival [31]. Furthermore, intracellular NF-kB activation has been described as a molecular mechanism by which inflammatory stress leads to renal injury [32]. Meanwhile, physiologically, inflammatory factors such as TNF-a play a major role in the regulation of immune responses, and the association between inflammation is shown to be closely related to abnormal TNF-a expression [33].…”
Section: Discussionmentioning
confidence: 91%
“…The study also found that NF-kB, in addition to its role mediated by TLR4, is a transcription factor that plays an important role in inflammation, immunity, cell proliferation, differentiation, and survival [31]. Furthermore, intracellular NF-kB activation has been described as a molecular mechanism by which inflammatory stress leads to renal injury [32]. Meanwhile, physiologically, inflammatory factors such as TNF-a play a major role in the regulation of immune responses, and the association between inflammation is shown to be closely related to abnormal TNF-a expression [33].…”
Section: Discussionmentioning
confidence: 91%
“…After the membranes were rinsed with TBST, they were incubated with horseradish peroxidase (HRP)-tagged anti-rabbit secondary antibody (concentration: 1:300) for 1 hour. Finally, the bands were visualized with the electrochemiluminescence automatic chemiluminescence imaging analysis system (Tanon, Shanghai, China) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hematoxylin-eosin (H&E), Masson’s trichrome, and periodic acid Schiff (PAS) staining kits were obtained from Solarbio Life Science (Beijing, China) [ 16 ]. Harvested lung tissue samples were fixed and mounted.…”
Section: Methodsmentioning
confidence: 99%